The Impact of Digital marketing Strategies on School Image - Denisa Nurfitriani (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
This study aims to determine the effect of digital marketing strategies on the image of SD IT An-Nahar Pangandaran. Digital marketing strategies have become an important communication tool in building and strengthening the image of educational institutions, especially in today's digital era. This study employs a quantitative approach using a correlational method. The research sample consists of parents of students who are the target recipients of the school’s digital promotional information. Data collection techniques involve distributing questionnaires via Google Forms, which are then analyzed using Pearson Product Moment correlation tests. The results of the study indicate a positive and significant relationship between digital marketing strategies and school image. The correlation coefficient value of 0.771 indicates a strong relationship, while the significance value of 0.000 (p < 0.05) indicates that the relationship is significant. This means that the better the implementation of digital marketing strategies, the more positive the school's image in the public eye. Digital marketing strategies influence school image by 77.1%, while the remaining 22.9% is influenced by other factors outside the variables studied. This study concludes that the social media-based digital marketing strategies implemented by SD IT An-Nahar Pangandaran—through platforms such as Instagram, Facebook, and YouTube—play an important role in shaping the public's positive perception of the institution. Therefore, strengthening the quality and consistency of digital marketing strategies is highly recommended to support the school's existence and competitiveness in the era of information technology.